Simulasi Data Curah Hujan Harian Menggunakan Stokastik Rantai MArkov Dengan Orde 3 x 3 (Studi Kasus : Daerah Aliran Sungai Kampar) - Rahmad Sandi; Bambang Sujatmoko; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The purpose of this study is to predict daily rainfall data and gain an overview of the parameters of daily rainfall simulation models to investigate two state, the dry state and the wet state. Analysis of daily rainfall simulation models in the Kampar river basin consists of two main models, namely simulated rainy days and dry days and simulation of the rainfall with Markov chain . Daily rainfall data 1983 to 2010. The stations are Koto Baru Station, Muara Lembu Station, Pasar Kampar station, Lipat Kain station. Rainfall data were divided into 4 length data 10, 15, 20 and 27 years. Each time series was constructed such that the events in question had the same opportunities as continuos recording results. Rainfall simulation results were tested using Chi Square test. With the increase in length of data used, generally will result in the value of Chi-Square are smaller and have a smaller error rate..Keywords: dry state, wet state, Markov chain, length of data, chi squared test